Making Sense of One's Place in an Educational Opportunity Program. (November 2019) - Todorova, Ralitsa
A college degree has been shown to decrease the income gap, but disadvantaged students are at a greater risk of dropping out of college. This study explores meaning-making of students in an educational opportunity program (EOP), the Search for Education Elevation and Knowledge (SEEK) in the City University of New York system. It is important to examine the experiences of students who are receiving additional support to understand how they develop through this complex transition process. Forty-six first-year SEEK students and 38 upperclassmen responded to a set of five narrative prompts of different genres. Using values analysis, the data showed that over half of the values guiding participants' narratives (53.30%) discussed the many benefits of SEEK and the sources of support youth rely on. Participants used the genres to express the complexities of transitioning to college as freshman, along with a settling in the later years. The findings of this study demonstrate youth perspectives on the ways in which EOPs can significantly contribute to student retention.